2006
DOI: 10.1002/biof.5520270118
|View full text |Cite
|
Sign up to set email alerts
|

The effect of plant cytokinin hormones on the production of ethylene, nitric oxide, and protein nitrotyrosine in ageing tobacco leaves

Abstract: Transgenic plants with genetically increased or decreased levels of cytokinins were used to investigate the effect of cytokinin level on the production of ethylene, a plant hormone with suggested role in senescence, and the production of nitric oxide, potentially important signalling and regulatory molecule. The production of these gases was followed during the course of leaf development and senescence. The production of ethylene and nitric oxide is under genetic control of genes other than those involved in r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(15 citation statements)
references
References 26 publications
1
14
0
Order By: Relevance
“…Presumably, CKs activate plasma membrane H1-ATPase through decreasing NO levels in guard cells, and then stimulate stomatal opening in darkness. Wilhelmova et al [44] reported similar results in transgenic tobacco plants. Negative interaction between NO and CKs was evident during leaf development as increased NO production reduced CKs level in aging leaves.…”
Section: No-phytohormone Cross Talk Under Drought Stressmentioning
confidence: 60%
“…Presumably, CKs activate plasma membrane H1-ATPase through decreasing NO levels in guard cells, and then stimulate stomatal opening in darkness. Wilhelmova et al [44] reported similar results in transgenic tobacco plants. Negative interaction between NO and CKs was evident during leaf development as increased NO production reduced CKs level in aging leaves.…”
Section: No-phytohormone Cross Talk Under Drought Stressmentioning
confidence: 60%
“…3 A and B). In addition, Wilhelmova et al (44) also found a negative correlation between cytokinin levels and NO production using transgenic tobacco plants with genetically increased or decreased levels of cytokinins. Clearly, the observations from the experiments applying exogenous NO or cytokinins are inconsistent with the results obtained using mutants or transgenic plants with altered NO or cytokinin levels.…”
Section: Discussionmentioning
confidence: 97%
“…2). 50 NO interacts with various stress responsive signal networks, chiefly salicylic acid (SA), jasmonic acid (JA), ethylene and the coordination of secondary signal molecules such as cADP ribose, cGMP and Ca…”
Section: Interplay Of No With Phytohormonesmentioning
confidence: 99%